Patient and public involvement in lifestyle randomized controlled trials: a systematic review. - Bouzalmate-Hajjaj, Amira; Cano-Ibáñez, Naomi; Khan, Khalid Saeed; Bueno-Cavanillas, Aurora; Guijarro, Paloma Massó (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Background: Motivating patients to take part in randomized controlled trials (RCTs) is challenging. Patient and public involvement (PPI), recommended for reporting since 2011, may potentially improve the recruitment and retention of participants in research. Aim: In this systematic review we aimed to identify the extent of PPI reported in RCTs of lifestyle interventions amongst adults and its impact on enrolment and retention rates. Methods: After prospective registration in PROSPERO (CRD42022359833), we searched the MEDLINE, Scopus, Web of Science, and Cochrane Library databases from inception to December 2022. We included RCTs with dietary interventions, with or without physical activity, and with or without behavioural support, among adults with overweight, obesity, or metabolic syndrome. Data extraction and study quality assessment were performed independently by two reviewers. Results: Of 1063 records, 26 RCTs (12,100 participants) were included. Among these, 22 were published after 2011. Of the total, 17 (65%) RCTs mentioned PPI directly (two studies) or indirectly. The methodological quality was high in 13 studies (50%), with no significant differences in PPI (p-value = 0.3187). The enrolment rate was no different but the median retention rate was high among RCTs with PPI (0.90; 95% CI 0.86–0.95) compared to those without (0.83; 95% CI 0.70–0.87) (p-value = 0.0426). Conclusion: PPI improved the retention of participants in RCTs with lifestyle interventions. However, its impact on enrolment was not clear. Overall, PPI should be encouraged in the RCT research process.